(untitled) (Swiss Medical Weekly, 2011)
PRINCIPLES: Bone and joint problems in Parkinson’s disease (PD) are manifold: decreased mobility, abnormal posture, as well as the risk of falling may cause both acute and chronic damage to the musculoskeletal system. In patients with Parkinson’s disease, postural instability and falls are frequently observed. The aim of the study was to review the literature with respect to the bone health and risk of fractures in these patients. METHODS: We conducted a review on bone health in patients with Parkinson’s disease. RESULTS: There is evidence that patients with PD have an increased risk of fractures, especially of the hip, due to the elevated risk of falling. While rigidity, bradykinesia and postural instability (but not tremor) predict falls, fractures also correlate with bone mineral density, which is generally lowered in this group of patients as compared to age- and sex-matched controls. Typically PD patients have “high turnover osteoporosis” due to several causes. CONCLUSIONS: Any newly diagnosed patient with PD should be evaluated for the risk of falling and osteoporosis and routinely be supplemented with vitamin D. In the case of osteoporosis, blood samples for detecting underlying and treatable conditions should be taken and bisphosphonates administered to the patient. It is unclear whether drugs typically used for PD provoke or worsen osteoporosis. Nevertheless, every long-term medication should undergo safety studies to demonstrate lack of negative interference with bone metabolism. Drug admission authorities should demand these data when registering new substances or when renewing old admissions.